2009
DOI: 10.1021/la803360n
|View full text |Cite
|
Sign up to set email alerts
|

Specific ζ-Potential Response of Layer-by-Layer Coated Colloidal Particles Triggered by Polyelectrolyte Ion Interactions

Abstract: The zeta-potential of PSS/PAH and PSS/PDADMAC coated silica particles was studied in the presence of ClO4(-) and H2PO4(-) salts. In the presence of ClO4(-), layer-by-layer (LbL) coated silica particles with PDADMAC as the top layer show a reversal in the surface charge with increasing salt concentration but remain positive in phosphate solutions. LbL particles with PAH as the top layer become, however, negative in the presence of H2PO4(-) but retain their positive charge in the presence of ClO4(-). Charge reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 29 publications
3
41
0
Order By: Relevance
“…P‐NMR studies have revealed that interactions with phosphates occur in the whole range of pH where a typical synthetic polyamine, polyallylamine (PAH), is protonated and phosphate is anionic (≈4–9) . On the other hand, this specific interaction between polyamines and phosphates was reported to reverse the surface charge in layer‐by‐layer polyelectrolyte multilayers . Furthermore, the specific adsorption of phosphate anions onto amino‐terminated self‐assembled‐monolayers, partially reversing the surface charge and even enhancing the adsorption of positively charged proteins, was demonstrated …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…P‐NMR studies have revealed that interactions with phosphates occur in the whole range of pH where a typical synthetic polyamine, polyallylamine (PAH), is protonated and phosphate is anionic (≈4–9) . On the other hand, this specific interaction between polyamines and phosphates was reported to reverse the surface charge in layer‐by‐layer polyelectrolyte multilayers . Furthermore, the specific adsorption of phosphate anions onto amino‐terminated self‐assembled‐monolayers, partially reversing the surface charge and even enhancing the adsorption of positively charged proteins, was demonstrated …”
Section: Introductionmentioning
confidence: 99%
“…[17] On the other hand, this specific interaction between polyamines and phosphates was reported to reverse the surface charge in layerby-layer polyelectrolyte multilayers. [18] Furthermore, the specific adsorption of phosphate anions onto amino-terminated selfassembled-monolayers, partially reversing the surface charge and even enhancing the adsorption of positively charged proteins, was demonstrated. [19] Learning about the physicochemical nature of the interaction between phosphates and polyamines and how it behaves within nanoconfined environments is the first step in understanding these fundamental biological interactions and in devising new types of synthetic biosensors for phosphate-bearing molecules.…”
Section: Introductionmentioning
confidence: 99%
“…According to the layer by layer formation mechanism has been applied successfully on fabrication of nanocomposites with thin layer [28,29], the similar method was used for coating ZnS shell on ZnS:Cu core. The formation mechanism of ZnS shells coated on the surface of ZnS:Cu NCs can be explained as follows: Firstly, because of the molar ratio of reactant (nS/nZn>1), many S 2− dangling bonds were existed on the surface of ZnS:Cu NCs (Fig.…”
Section: Formation Mechanism Of Zns Shellsmentioning
confidence: 99%
“…LBL films have been employed for the coating of colloids and thereof fabrication of micro and nanocapsules, [10] the fabrication of membranes for reverse osmosis, [11] or just as a versatile tool for the non-covalent modification of surfaces. [12] LBL films can be assembled on a large variety of charged surfaces including polyelectrolyte brushes.…”
Section: Introductionmentioning
confidence: 99%